Music makers: living legends of Indian classical music - Roy, Ashok (Living legends of Indian classical music, 2004)
Articles on life and work of 21 Indian classical musicians.
Articles on life and work of 21 Indian classical musicians.
Keywords: Music / India / History and criticism. / http://id.loc.gov/authorities/subjects/sh89006854; Musicians / India / Pictorial works.; Musicians / India / Interviews.; Musicians / India / Biography. / http://id.loc.gov/authorities/subjects/sh2008108143